The Role of Mobile Instant Messaging (Mim) Application in Enhancing Technical Students’ Frequency of Communication, Social Connectedness and Group Attitude: A Proposed Framework - Noor Raha, Mohd Radzuan; Zarina, Mohd Ali; Abdullah Adnan, Mohamed; Nurkarimah, Yusof; Mohd Asyraf, Othman (2015)
Mobile instant messaging (MIM) has become an essential part of everyday life in this digital era. This current trend has been widespread among young adults in developed and developing nations as a result of overwhelming smartphone penetration. Therefore, it is not surprising to find students at tertiary level, whose lives revolve around gadgets and devices hence often referred to as ‘digital natives’, to be particularly influenced by technology in the way they communicate. For a discipline such as engineering which places an emphasis on communication and teamworking skills, greater social connectedness and positive attitude towards group may promote ‘situated learning’ where learning occurs outside the classroom. However, the language teacher often has little knowledge of the frequency of communication students engage in, how they connect among peers in the same group and students’ attitude towards their group because most of this kind of communication takes place outside of the classroom. Thus, it is imperative that English language practitioners, who teach language and communication skills to technical students, study how elements of social connectedness and attitude towards group among students are related to the way students communicate in a mobile environment using instant messaging. This paper presents a framework for measuring frequency of students’ group communication via MIM environment based on six communication types in relation to their social connectedness and attitudes towards their respective groups in which peers are of similar level of proficiency.